A Chromosome-Level Genome Assembly of the Mandarin Fish (Siniperca chuatsi) - Ding, Weidong; Zhang, Xinhui; Zhao, Xiaomeng; Jing, Wu; Cao, Zheming; Li, Jia; Huang, Yu; You, Xinxin; Wang, Min; Shi, Qiong; Bing, Xuwen (Frontiers in Genetics, 2021)
The mandarin fish, Siniperca chuatsi, is an economically important perciform species with widespread aquaculture practices in China. Its special feeding habit, acceptance of only live prey fishes, contributes to its delicious meat. However, little is currently known about related genetic mechanisms. Here, we performed whole-genome sequencing and assembled a 758.78 Mb genome assembly of the mandarin fish, with the scaffold and contig N50 values reaching 2.64 Mb and 46.11 Kb, respectively. Approximately 92.8% of the scaffolds were ordered onto 24 chromosomes (Chrs) with the assistance of a previously established genetic linkage map. The chromosome-level genome contained 19,904 protein-coding genes, of which 19,059 (95.75%) genes were functionally annotated. The special feeding behavior of mandarin fish through the interaction of a variety of sense organs (such as vision, smell, and endocrine organs). Through comparative genomics analysis, some interesting results were found. For example, olfactory receptor genes (especially the beta and delta types) underwent a significant expansion, and endocrinology/vision related npy, spexin and opsin genes presented various functional mutations. These may contribute to the special feeding habit of the mandarin fish by strengthening the olfactory and visual systems. Meanwhile, previously identified sex-related genes and quantitative trait loci (QTLs) were localized on the Chr14 and Chr17, respectively. 155 toxin proteins were predicted from mandarin fish genome. In summary, the high-quality genome assembly of the mandarin fish provides novel insights into the feeding habit of live prey and offers a valuable genetic resource for the quality improvement of this freshwater fish.